CLINICAL CONUNDRUM OF STEROID RESISTANT TESTICULAR ADRENAL REST TUMOURS (TARTS): CASE SERIES - Bahrudin, Mohd Fyzal; Othman, Abdul Rahim Mohd; Abdullah, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Testicular adrenal rest tumours (TARTs) are benign intratesticular masses that occur in male patients with congenital adrenal hyperplasia (CAH), with more than 90% of cases caused by a deficiency of 21-α-hydroxylase. The presence of TART is an important complication leading to irreversible gonadal dysfunction and infertility. TARTs appear to be associated with poor hormonal control with concomitant elevated ACTH. The current mainstay of therapy is intensified glucocorticoid therapy. We describe two challenging cases of steroid-resistant TARTs. CASE Case 1 is a 25-year-old male with classical CAH diagnosed at 7 weeks of life. At age 12, he was diagnosed with TARTs. With a 17-OHP elevated to >60.6 nmol/L, his glucocorticoid dose was intensified with dexamethasone 0.5 mg ON for 5 years together with fludrocortisone. The latest 17-OHP was 436.7 nmol/L (1-10), ACTH 80.6 pmol/L (1.6-13.9), Direct renin >550 mU/L (5.3-99.1) and testosterone 21.64 nmol/L (0.58 - 31.28). Testicular ultrasonography demonstrated unresolved TARTs 1.0 x 1.1 x 1.4 cm (right) and 1.3 x 1.2 x 2.3 cm (left). Dexamethasone was subsequently switched to prednisolone 2.5 mg BD together with a referral to the urology team for consideration of testicular-sparing surgery or semen cryopreservation. Case 2 is a 20-year-old male with classical CAH diagnosed as a one-month-old infant and diagnosed with TARTs at age 13 years. Apart from fludrocortisone, his glucocorticoid therapy was intensified with dexamethasone 2.5 mg ON (tapering dose) for 5 years with his latest 17-OHP 116.4 nmol/L, testosterone 23.06 nmol/L, ACTH 128.9 pmol/L and Renin 47.2 mU/L. Testicular ultrasonography revealed increased size of TARTs 2.0 x 1.9 x 3.3 cm (right) and 1.7 x 1.5 x 2.9 cm (left). His case was complicated by exogenous Cushing syndrome secondary to dexamethasone. Dexamethasone was switched to prednisolone 2.5 mg BD with a referral to the urology team for co-management. CONCLUSION Intensified glucocorticoid therapy has led to tumour size reduction and improved testicular function in only a subset of patients. However, this approach potentially leads to serious side effects. Further research should aim to identify pharmacological alternatives that can effectively prevent the development of TARTs and treat existing TARTs to improve fertility outcomes.